Sweet lies: neural, visual, and behavioral measures reveal a lack of self-control conflict during food choice in weight-concerned women - Laura Nynke eVan Der Laan; Denise T. D. eDe Ridder; Lisette eCharbonnier; Max A. eViergever; Paul A.M. eSmeets; Paul A.M. eSmeets (Frontiers in Behavioral Neuroscience, 2014)
Despite their intentions, weight-concerned individuals generally fail to control their eating behavior. However, it is unknown whether this failure is due to a lack of effortful self-control, or to not experiencing an internal conflict between weight goals and food temptations. The present study used fMRI, eye tracking and reaction times to assess the degree of conflict experienced by weight-concerned women during food choices that posed either a self-control dilemma (i.e., requiring a choice between healthy and palatable foods), or not. Contrary to the common assumption in self-control theory that food choices posing a self-control dilemma evoke internal conflict, we found that choices requiring self-control induced no conflict, as demonstrated by lower reaction times, fixation durations, number of gaze switches between snacks, and lower activation of the anterior cingulate cortex. Self-control failure might be due to a lack of experienced conflict, rather than to failing to act upon the perception of such conflict. This implies that effectiveness of weight maintenance interventions might be improved if they also focus on increasing the ability to detect a self-control dilemma, in addition to the current focus on increasing self-regulatory capacity.